What makes a specialised emergency plan effective?—A case study of railway operation in 33 prefectural cities in China - Cuixi Li; Yibao Wang; Wen Qing; Chong Li (PLoS ONE, 2025)
Emergency response plans play a crucial role in mitigating safety risks associated with urban rail transport operations and effectively responding to emergencies in underground spaces. This study evaluates and analyzes the emergency response plans for rail transit operations in 33 cities in China, focusing on the consistency and completeness of the plans. The evaluation index system for Urban Rail Transit Operation Emergency Plans (URTOEPs) consists of 9 primary variables and 42 secondary variables, constructed based on the text analysis and the Policy Model Consistency (PMC) index model. It fills the gap of more fragmented analysis and less holistic quantitative assessment in the research of established urban rail transit emergency plans. The results indicate that URTOEPs are well-designed, but there is still room for improvement. The mean PMC index value for 33 URTOEPs is 7.83, which reflects a good grade overall. Of these, 11 URTOEPs achieved an excellent grade while 22 were rated as good. Meanwhile, based on the mean PMC index of first-level variables and the PMC-surface diagrams of six representative plans, the emergency plans need significant improvement in restoration and reconstruction, plan application, and preventive preparedness. This study enriches the research related to text quality assessment of emergency plans, identifies structural deficiencies in the plan system through quantitative assessment, and provides empirical references for the optimization of urban rail transit emergency plans and the formulation of policies related to urban risk management.